Overexpression of REIC/Dkk-3 suppresses the expression of CD147 and inhibits the proliferation of human bladder cancer cells - Horikawa, Yuhei (Oncol Lett, 2017)
Our group previously developed an adenoviral vector encoding the REIC/Dkk-3 gene (Ad-REIC), a tumor suppressor, for cancer gene therapy. The Ad-REIC agent induces apoptosis and inhibits invasion in a number of cancer cell lines; however, the molecular mechanisms underlying its effects remain unclear. Cluster of differentiation 147 (CD147), also known as extracellular matrix metalloproteinase inducer (EMMPRIN), is a key molecule that promotes cancer proliferation and invasion. In order to elucidate the therapeutic mechanism of Ad-REIC, its effect on the expression of CD147 in human bladder cancer KK47 cells was investigated. Treatment with Ad-REIC markedly downregulated the expression of CD147 and significantly inhibited cellular proliferation. Since the expression of CD147 is reported to be under the positive control of mitogen-activated protein kinase (MAPK) signaling and the c-Myc protein, the correlations between the expression of CD147 and the activation of MAPKs or the expression of c-Myc were examined. Unexpectedly, no positive correlation was observed between the level of CD147 and the potential regulators that were assessed, indicating that another signaling pathway is responsible for the downregulation of CD147. The results from the present study demonstrate that Ad-REIC treatment can significantly downregulate the expression of CD147 in bladder cancer cells. Downregulation of the cancer-progression factor CD147 may be a novel mechanism that underlies the therapeutic effects of Ad-REIC treatment.